Strategi Misi Penginjilan Yesus: Sebuah Studi Eksposisi Matius 9:35-37 - Samuel Purdaryanto; Hariyanto Hariyanto; Deice Miske Poluan (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
A mission is the sending of a church for believers to preach the gospel in the midst of the world to the unbelievers. The implementation of the mission can be realized properly, a strategy or steps are needed to achieve the goal. From the existing data, in Indonesia alone there are still 131 neglected tribes who have not heard the gospel news. Looking at this data, the mission strategy of preaching the gospel is still very much needed to increase the number of existing evangelistic mission strategies. This research uses a qualitative approach with descriptive analysis methods through exposition studies. The author conducted an expositional study of the Gospel of Matthew 9:35-38 with the OIA model (observation, Intepretation, Application), to find a mission strategy for preaching the gospel of Jesus. The results of this study found a mission strategy for preaching the gospel of Jesus which is divided into three steps. Compassion as the basis of the strategy of preaching the gospel, moving to reach all places, and preaching and teaching. These findings encourage every Christian to become more active in missionary ministry. ABSTRAKMisi merupakan pengutusan gereja bagi orang percaya untuk memberitakan Injil di tengah dunia kepada mereka yang belum percaya. Pelaksaan misi dapat terealisasi dengan baik, diperlukan strategi atau langkah-langkah untuk mencapai tujuan tersebut. Dari data yang ada, di Indonesia saja masih terdapat 131 suku terabaikan yang belum mendengar berita Injil. Melihat data ini, strategi misi pemberitaan Injil masih sangat diperlukan untuk menambah jumlah strategi misi penginjilan yang sudah ada. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisa deskriptif melalui studi eksposisi. Penulis melakukan studi eksposisi terhadap Injil Matius 9:35-38 dengan model OIA (observasi, Intepretasi, Aplikasi), untuk menemukan strategi misi pemberitaan Injil Yesus. Hasil penelitian ini menemukan strategi misi pemberitaan Injil Yesus yang dibagi dalam tiga langkah. Belas kasih sebagai dasar strategi memberitakan Injil, bergerak menjangkau segala tempat, serta  memberitakan dan mengajar. Temuan ini mendorong setiap orang Kristen untuk semakin giat dalam pelayanan misi. Kata-kata kunci: Misi; Strategi, pemberitaan; belas kasihan; mengajar